2019
DOI: 10.32598/irj.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Semmes-Weinstein Monofilaments and Tuning Fork on Pressure and Vibration Sensation Measurements in Diabetic Patients

Abstract: Sensory neuropathy is the major cause of ulceration in diabetic patients. Periodical sensory examination is an appropriate method to detect neuropathy and decrease the risk of diabetic foot ulcer. Semmes-Weinstein Monofilaments (SWM) and tuning fork on/off test are widely used to assess pressure and vibration sensitivity. The present study evaluated the interand intra-rater reliability of SWM and tuning fork to measure pressure and vibration sensations in diabetic patients. Methods: Following ethical approval,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…To help health care professionals select the optimal tests of sensibility, there have been ongoing discussions on the psychometric properties of sensibility tests, such as reliability and validity, in a variety of injuries and other neurologic conditions. 19 , 20 , 21 , 22 However, in the context of upper limb PNI, there still exist uncertainties in choosing the optimal sensibility tests. For example, Jerosch-Herold 4 identified that 2-PD has limited validity and responsiveness yet remains widely used in the PNI setting.…”
mentioning
confidence: 99%
“…To help health care professionals select the optimal tests of sensibility, there have been ongoing discussions on the psychometric properties of sensibility tests, such as reliability and validity, in a variety of injuries and other neurologic conditions. 19 , 20 , 21 , 22 However, in the context of upper limb PNI, there still exist uncertainties in choosing the optimal sensibility tests. For example, Jerosch-Herold 4 identified that 2-PD has limited validity and responsiveness yet remains widely used in the PNI setting.…”
mentioning
confidence: 99%
“…The previous study related vibration test by using tuning fork demonstrated that within-day intra-and inter-rater reliability of tuning fork were excellent. However, between-days intra-and inter-rater reliability were moderate and poor, respectively [3].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-class Correlation Coefficients (ICC) and Standard Error of the Mean (SEM) were calculated to evaluate within and between subject inter and intra rater reliability of 10g Monofilament and Neo-Vibrometer. Based on Rosner's classification, ICC≥0.75 represent excellent, 0.4≤ICC<0.75 indicate fair to good, and <0.4 demonstrate poor reliability [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical protocols such as Semmes-Weinstein Monofilament Examination (SWME), Tuning Fork, and Vibration Perception Thresholds (VPT) are also widely used due to their low cost of tools (Lavery and Armstrong, 2012;Bagherzadeh Cham et al, 2016). Other clinical detective devices liking Quantitative Sensory, Electromyogram and Electrocardiograph, Ergograph, Force Plate, and Plantar Pressure Plate are also used for DPN's evaluate (Lavery et al, 2002;Turgut et al, 2009;Kuhn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%